Membaca Animo Pemuda dalam Memberikan Persembahan Persepuluhan - Seri Damarwanti (SANCTUM DOMINE: JURNAL TEOLOGI, 2015)
Giving tithes offering is a God’s commandment to man that must be taught to every generation. Basically, giving is loving action, loyalty and obedience to God . The practice or implementation of giving tith offering among the younger generation is the result of various factors that preceded before the practice. Based on scientific studies conducted in the field of literatures and observations in the population, the awareness come from inside of them to engage God's mission and stewardship in the church. It takes the place of the most dominant factor that dominates others.